Karakter dan Model Bimbingan/Pendidikan Islam bagi Anak Cerdas dan Berbakat - Adha, Hijazzi Lutfiah Izyul; Hurairah, Abi; Rohman, Ilham Abdur (ANWARUL, 2022)
Islamic education which has or is known by its characteristics, symbolizes something that is inherent in itself. While education in Islam is education that comes directly from Allah SWT. Al-Quran and Sunnah in the development of Islamic education have a character where humans are directly related to their creation through the teachings that have been taught in Islam, such as prayer, reciting and others. On this occasion, the discussion about the characteristics and models of Islamic education guidance for intelligent and gifted children. Hearing the word Islamic education, of course, we are immediately directed to special Islamic educational institutions, namely madrasas, Islamic education is widely taught in Islamic madrasas, ranging from MI, MtS, and MA. Islam really appreciates science, Islam also elevates the degree of people who are knowledgeable and do good deeds. In Islam, if there are students who are talented and intelligent in the religious and social sciences and have good morals, then they are noble in the sight of Allah SWT.